Measurement of income distribution in supranational entities: The case of the European Union - Andrea Brandolini (Luxembourg Income Study (LIS), 2006)
Greater social cohesion is an explicit goal of the European Union. Progress is monitored considering the performance in each member country on the basis of national indicators; EU-wide estimates of inequality and poverty play no role. Yet this is a basic information to evaluate the progress of the Union toward grater social cohesion. This paper examines the methodological requirements of this evaluative exercise, and provides the first estimates of inequality and poverty in the enlarged European Union as if it was a single country.
Keywords: 330; Einkommensverteilung; Verteilungsgerechtigkeit; Armut; EU-Staaten